Preparation of a superhydrophobic and superoleophilic polyester textile by chemical vapor deposition of dichlorodimethylsilane for Water–Oil separation. (1st February 2019) - Zareei Pour, Faride; Karimi, Hajir; Madadi Avargani, Vahid
Graphical abstract: Micro/nanostructure rough polyester textile with superhydrophobic and superoleophilic properties was prepared by CVD of DMDCS under certain conditions and then tested in different ways for water-oil separation application. Abstract: Oil–water separation is an important concept because of the growing effluents of industrial oily wastewater and frequent oil spills. Recently, oil–water separation routes have been developed by changing the wettability of membranes via surface modifications. Herein, a facile, handmade and rapid chemical vapor deposition method to make a PVC-top-coated textile for separating oil from oil–water mixtures is reported by using DMDCS as the coating. The tuning of the CVD process parameters (efficient reaction time and DMDCS concentration) enables the textile surface to have superhydrophobicity and superoleophilicity properties. These properties were evaluated by the contact angle measurement and practical tests. The FESEM, EDAX, ATR, TGA, and AFM analyses were also presented to characterize the coated textile. The successful separation of a 20 mL oil–water solution, without any external force, in 4 min was achieved. Results from the study also reveal that the coated textile has self-cleaning, high reusability, and an average intrusion pressure of 1.36 kPa features. The fabrication of silicone layer on the surface of the textile with silanes proved to be a simple route for the preparation of the superhydrophobic membranes.